Psychological resources of oncological patients at the palliative stage of treatment - Нечитайло, Олександра; Mukharovska Інна (Psychosomatic Medicine and General Practice, 2024)
Oncological diseases are the leading cause of mortality in the world and in Ukraine. This problem requires the development of comprehensive strategies for combating and improving the medical and psychosocial support of patients. Advances in medicine allow more people with serious illnesses to receive palliative care at the end of life. Studying and understanding the psychological resources that contribute to improving the quality of life of cancer patients at the palliative stage is critically important for ensuring their comfort and developing more effective methods of psychological support in the palliative field.